Information System for Prevention of National Healthcare Insurance Fraud Among Inpatients of Advanced Referral Health Services - Budi Santoso; Yulita Hendrartini; Bambang Udji Djoko Rianto; Laksono Trisnantoro (Academic Hospital Journal, 2018)
Background: The National Health Insurance (JKN) was started from January 1st, 2014, however every year there was a deficit between the income of the Social Security Administrator Healthcare (BPJS Kesehatan) and the money paid to healthcare facilities. One of the causes was the potential for JKN fraud in inpatient services at advanced referral health facilities (FKRTL). As a response, the Ministry of Health, the Corruption Eradication Commission (KPK) and other JKN stakeholders currently are developing a JKN fraud prevention, early detection, investigation and action system.Objective: This research aimed to analyze the implementation of the new information system for potential JKN fraud prevention and detection in inpatient services for JKN participants in RSUP Dr. Soeradji Tirtonegoro as an example of FKRTL.Design: This study used cross-sectional methods in assessing JKN fraud in single episodes of patient care by using JKN fraud indicators in the information system. We identified potential JKN fraud during April-July 2017 from JKN claim data. Reliability of information system was assessed by HOT-Fit research questionnaire (Human Organization Technology and Benefit) and Stata® software.Results: The data shown there was a significant decrease in potential JKN fraud conducted by FKRTL between April-July 2017: in April 14 findings, May 8 findings, June 1 findings, and July there were no findings. Prevention and early detection of potential JKN fraud among hospitalized JKN participants were conducted effectively by using an information system that contains indicators of JKN fraud. Reliability analysis of information system on the patient administration officers (TURP), BPJS Kesehatan officers and hospital internal verification officers resulted in alpha Cronbach value of > 0.8.Conclusions: The results show that the information system is reliable to prevent and early detect potential JKN fraud in inpatient services for JKN participants in FKRTL. Information system is effective and reliable for prevention and early detection potential National Health Insurance fraud in service of inpatient advanced referral health services.